A fragilidade e suas representações para idosos domiciliados no contexto da estratégia de Saúde da Família - Oliveira, Luciane Paula Batista Araujo de (2008)
This study aims to analyze social representations of elders to their fragile situation at home, with the presence of one or more characteristics, as defined by the Brazilian Ministry of Health. It is a descriptive and qualitative study, based on methodological -principles of the Theory of Social Representations. Setting was the homes of elderly residents in the area ascribed to a Family Health Unit (FHU) in the city of Natal. A total of 10 elderly subjects, whose choice was intentional and according to the need for USF home visit in a period of time, considering the saturation process of the information. As collection procedures were used the semi-structured interview and participant observation in accordance with the ethical rules of Resolution No. 196/96, with the assent of the Ethics and Research UFRN. To analyze the results, it was used the thematic content analysis in the aspect of preparation of representations, focusing on the totality of the discourse of the subjects. The results indicate that most study participants felt difficult to give meaning to the terms weakness and to be weak, although many present one or more aspects of the syndrome of frailty. From the content analysis of participants speeches in this study, we achieved the following categories: fragility as illness and disease as aging, aging and frailty as causes of changes and difficulties in daily life, the presence of family life in the fragile elderly, fragility as weakness and the risk for falls, the perception of being weak like a different person in addition to the absence of fragility in elderly life. Thus, through the processes of anchoring and objectification, the "fragile being" became familiar and concrete, showing that the meaning of weakness, besides the scientific definition found in the reified universes, can be reinterpreted and built within the consensus universes. About the care received by the staff of Family Health, from the viewpoint of older people there seems to be an understanding about the role of professional nurses; on the other hand, older people often mention the role of the Community Health Agent